Hierarchical NiO/TiO2-Biomass-Derived Porous Carbon Composite with Improved Electrochemical Kinetics for Energy Storage Applications - Nurdin, Muhammad; Maulidiyah, Maulidiyah; Watoni, Abdul Haris; Zakir, Muhammad; Muliadi, Muliadi; Muzakkar, Muhammad Zakir; Azmi, Khusnul Ulul; Edihar, Muh; Zulfan, Ahmad (Pandawa Institute, 2026)
The development of high-performance and sustainable anode materials remains a crucial challenge for next-generation energy storage systems. In this study, NiO/TiO₂–biomass-derived porous carbon (BPC) composites were successfully synthesized using palm kernel shell-derived porous carbon as a conductive matrix. Structural and morphological characterizations confirmed the homogeneous distribution of NiO and TiO₂ crystals within the porous carbon framework. The FTIR and XRD analyses verified the presence of metal-oxygen bonds and high phase purity, while SEM revealed a well-developed porous structure. Electrochemical evaluations were performed in KOH solution using a three-electrode configuration. The optimized NiO-TiO2/BPC (1:2) electrode delivered a specific capacity of 7.76 mAh g⁻¹ at 10 mV s⁻¹ and sustained 3.59 mAh g⁻¹ at 80 mV s⁻¹, demonstrating favorable rate capability. Galvanostatic charge-discharge measurements further confirmed the improved performance, reaching 8.75 mAh g⁻¹ at 3 A g⁻¹. This enhanced electrochemical behavior is attributed to the synergistic integration of conductive porous carbon with electroactive NiO and TiO₂ phases. These findings indicate that the NiO-TiO₂/BPC composite functions as a hybrid alkaline electrode material and has potential for safe and sustainable aquatic energy storage devices.